2005
DOI: 10.1038/sj.ejhg.5201471
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional phenotypic analysis and functional categorisation of mutations reveal novel genotype–phenotype associations in Rett syndrome

Abstract: We aimed to improve the understanding of genotype -phenotype correlations in Rett syndrome (RS) by adopting a novel approach to categorising phenotypic dimensions -separating typicality of presentation, outcome severity and age of onset -and by classifying MECP2 mutations strictly by predicted functional attributes. MECP2 mutation screening results were available on 190 patients with a clinical diagnosis of RS (140 cases with classic RS, 50 with atypical RS). 135 cases had identified mutations. Of the 140 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 31 publications
7
44
0
1
Order By: Relevance
“…Epilepsy was present in 70.4% of the cases. Among patients with the severe form, 81,4% had truncating mutations, and all but one with the R168X mutation presented it; they showed a median severity score of 15 (range, [12][13][14][15][16][17][18][19][20].…”
Section: Clinical Presentation Among Mecp2 Positive Rtt Patients (Gromentioning
confidence: 99%
See 2 more Smart Citations
“…Epilepsy was present in 70.4% of the cases. Among patients with the severe form, 81,4% had truncating mutations, and all but one with the R168X mutation presented it; they showed a median severity score of 15 (range, [12][13][14][15][16][17][18][19][20].…”
Section: Clinical Presentation Among Mecp2 Positive Rtt Patients (Gromentioning
confidence: 99%
“…Concerning the phenotype of specific mutations, several studies [14][15][16][17] showed that patients with the R133C and R306C mutations have better overall function. In general, the most severe outcomes were found with the R270X and R255X mutations [11,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Control samples used in statistical comparisons were 49 previously analysed (Knudsen et al, unpublished) healthy females age 19 -63 years (for buccal cell XCI data) and 153 normal healthy females (for blood XCI data), of whom 117 were anonymised blood donors (age 19 -55 years) and 36 were sampled from the set of individuals used in the buccal control set (age 19 -55).…”
Section: Subjectsmentioning
confidence: 99%
“…At present, all clinical details except for the general classification in classic, variant, or RTT-like cases, are available only for bank curators on the '' Additional info'', page. We are planning to create, for each case, a table with a set of clinical features and a related clinical score according to data in the literature [Charman et al, 2005;Colvin et al, 2003;Huppke et al, 2002;Kerr et al, 2001;Monros et al, 2001]. The new schedule will be freely available to the general public.…”
Section: Future Prospectsmentioning
confidence: 99%